2014
DOI: 10.7717/peerj.503
|View full text |Cite
|
Sign up to set email alerts
|

Stream grazers determine their crawling direction on the basis of chemical and particulate microalgal cues

Abstract: This study aimed to determine the association between herbivore behavior and cues from producers. We used stream grazer Glossosoma larvae and determined their crawling direction in relation to chemical and visual cues from microalgae. The experimental treatments included control (no cue), particulate (chemical and particulate cues), and dissolved (chemical cue) cues from microalgae. The experimental water samples were randomly placed into either arm of a Y-shaped channel, and the crawling direction of the graz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Another solution was to use isotopic values of herbivores as proxies for the isotopic values of algae (Vander Zanden and Rasmussen , Finlay ), and we used the ubiquitous Glossosoma scrapers, which are known to selectively feed on the algal portion of biofilms (Oemke , McNeely et al. , Katano and Doi ), to reflect algal δ 13 C and δ 15 N. We acknowledge that this approach may have introduced some error in our estimates as it assumes 100% herbivory by Glossosoma across streams. That assumption is unlikely to be true, leading to an overestimation of autochthonous contributions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another solution was to use isotopic values of herbivores as proxies for the isotopic values of algae (Vander Zanden and Rasmussen , Finlay ), and we used the ubiquitous Glossosoma scrapers, which are known to selectively feed on the algal portion of biofilms (Oemke , McNeely et al. , Katano and Doi ), to reflect algal δ 13 C and δ 15 N. We acknowledge that this approach may have introduced some error in our estimates as it assumes 100% herbivory by Glossosoma across streams. That assumption is unlikely to be true, leading to an overestimation of autochthonous contributions.…”
Section: Discussionmentioning
confidence: 99%
“…To improve source separation, we first incorporated a third marker (d 2 H), since the addition of H isotopes to stream food web studies has been shown to increase the resolution of dietary sources (Doucett et al 2007, Jardine et al 2009, Finlay et al 2010), but the source overlap remained. Another solution was to use isotopic values of herbivores as proxies for the isotopic values of algae Rasmussen 1999, Finlay 2001), and we used the ubiquitous Glossosoma scrapers, which are known to selectively feed on the algal portion of biofilms (Oemke 1984, McNeely et al 2006, Katano and Doi 2014, to reflect algal d 13 C and d 15 N. We acknowledge that this approach may have introduced some error in our estimates as it assumes 100% herbivory by Glossosoma across streams. That assumption is unlikely to be true, leading to an overestimation of autochthonous contributions.…”
Section: Methodological Limitations and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periphytic algae are the most important primary producers in stream ecosystems (Minshall, 1978; Vannote et al, 1980; Lange et al, 2011). Grazer-periphyton interactions in stream environments have been used as model systems to understand more general producer-herbivore interactions (Hart & Robinson, 1990; Feminella & Hawkins, 1995; Doi, Katano & Kikuchi, 2006; Doi & Katano, 2008; Katano & Doi, 2014). The influence of resources and grazing on the composition of periphyton assemblages can be assessed both taxonomically and with regard to functional groups (Passy, 2008), two parameters that can be affected by light, nutrients, and grazing regimes (Johnson, Tuchman & Peterson, 1997; Hollingsworth & Vis, 2010; Lange et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The patterns of macroinvertebrate spatial distribution are governed by multiple fluid flow, biologic, geomorphic, and chemical variables acting both independently and in combination [ Statzner et al ., ; Nikora , ; Holomuzki et al ., ; Katano and Doi , ]. Among these variables, open‐channel fluid flow conditions represent a major hydraulic gradient along which the benthic macroinvertebrate community is organized [ Rempel et al ., ].…”
Section: Introductionmentioning
confidence: 99%